Adipose Tissue Distribution and Survival Among Women with Nonmetastatic Breast Cancer. Issue 6 (25th April 2019) - Bradshaw, Patrick T.; Cespedes Feliciano, Elizabeth M.; Prado, Carla M.; Alexeeff, Stacey; Albers, Kathleen B.; Chen, Wendy Y.; Caan, Bette J.
Abstract : Objective: Previous studies of breast cancer survival have not considered specific depots of adipose tissue such as subcutaneous adipose tissue (SAT) and visceral adipose tissue (VAT). Methods: This study assessed these relationships among 3, 235 women with stage II and III breast cancer diagnosed between 2005 and 2013 at Kaiser Permanente Northern California and between 2000 and 2012 at Dana Farber Cancer Institute. SAT and VAT areas (in centimeters squared) were calculated from routine computed tomography scans within 6 (median: 1.2) months of diagnosis, covariates were collected from electronic health records, and vital status was assessed by death records. Hazard ratios (HRs) and 95% CIs were estimated using Cox regression. Results: SAT and VAT ranged from 19.0 to 891 cm 2 and from 0.484 to 454 cm 2, respectively. SAT was related to increased risk of death (127‐cm 2 increase; HR [95% CI]: 1.13 [1.02‐1.26]), but no relationship was found with VAT (78.18‐cm 2 increase; HR [95% CI]: 1.02 [0.91‐1.14]). An association with VAT was noted among women with stage II cancer (stage II: HR: 1.17 [95% CI: 0.99‐1.39]; stage III: HR: 0.90 [95% CI: 0.76‐1.07]; P interaction < 0.01). Joint increases in SAT and VAT were associated with mortality above either alone (simultaneous 1‐SD increase: HR 1.19 [95% CI: 1.05‐1.34]). Conclusions: SAT may be an underappreciated risk factor for breast cancer‐related death.